Pengetahuan Pasangan Usia Subur Tentang Deteksi Dini Kanker Rahim Dan Akses Layanan Pemeriksaan IVA/ Papsmear - Nurul Soimah (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2017)
Research using qualitative design of with focus group discution approach focused on fertile couples in the study group ‘Aisyiyah Ranting Gonggong, Bangunkerto, Turi, Sleman, March 2017 period. Informants were selected with purposive sampling technique, fertile couples aged between 16-40 years, FGD of 7 women of childbearing age and 1 male until saturated data obtained. Instrument guide FGD adopted from the “Mampu” program of ‘Aisyiyah Head of ‘Asyiyah Research Institute. Data analysis using Spradely Model, namely to verify for the meaning from data with domain analysis, record regularity, sort into the pattern, simplifying to the form of transcript, according to categories in te taxonomy, determine the theme of the findings (Sugiyono, 2008). The result of knowledge Knowledge of fertile couples is still lacking has not been information Suggestions of the leader of Aisyiyah Branch to add the material of ‘pengajian’ with reproductive health theme.Keyword: knowledge, early detection of cancer IVA test